Painful unilateral facial swelling due to superficial temporal artery thrombosis: a rare presentation of Antiphospholipid Syndrome - Lima, Helena da Cunha Lopes de; Pereira, Ana Clara Dias; Moura, Naiara Cunha de; Silva, Vivian Langue Rodrigues; Silva Junior, Hilton Mariano da (Headache Medicine, 2022)
IntroductionPersistent painful unilateral temporal swelling is rarely seen in clinical practice. Antiphospholipid syndrome (APS) is an autoimmune and systemic disorder that causes changes in blood clotting homeostasis, marked by arterial or venous thrombosis, gestational morbidity, and high and persistently positive serum levels of antiphospholipid antibodies (aPL). APS is more common in young women and middle-aged adults, with no preference for race. Among its clinical features, temporal artery thrombosis, associated with headache and temporal and hemifacial edema is extremely rare, with few publications worldwide on this topic.ObjectiveThis report aims to present the case of a unilateral painful facial edema due to thrombosis of the superficial temporal artery as an unprecedented manifestation of Antiphospholipid Syndrome. Thus, the only record in the English-language literature surveyed in the Pubmed database in July 2022 highlights the rarity of this APS presentation and the consequent challenge in suspecting the correct diagnosis for adequate treatment.Methods Case report. Data disclosure was authorized by the patient through an informed consent form.ResultsA 32-year-old woman was presented with pain in the right temporal region of her face. The pain was intense, daily and continuous, pulsating, without irradiation, which worsened with physical activity and presented partial relief with common analgesics. After 20 days, she developed a right pale temporal edema (Figure 1) associated with a significant worsening of pain and intense right unilateral headache attacks triggered by chewing and speaking. She has a history of deep vein thrombosis in the left lower limb. Physical examination and imaging tests showed significant cold edema of the right temporal region with asymmetry of the temporal muscles, which was extremely painful on palpation and made it difficult to open the mouth. There were no other changes in the general physical... (Too see the complete abstract, please, check out the PDF.)